Crowdsourced Water Level Monitoring in Kenya’s Sondu-Miriu Basin—Who Is “The Crowd”? - Weeser, Björn; Gräf, Jan; Njue, Naomi K.; Cerutti, Paolo; Rufino, Mariana C.; Breuer, Lutz; Jacobs, Suzanne R. (Frontiers in Earth Science, 2021)
Citizen science is gaining popularity as a way to engage people to participate in environmental projects. In addition to potential challenges regarding data quality and the choice of variables, a key factor in the success of participatory monitoring projects is the active participation of volunteers, the ‘citizen scientist’. To learn more about the motivation of citizen scientists to participate and their socio-economic background, a telephone survey was implemented with participants of a citizen science water-level monitoring program in the Sondu-Miriu basin, western Kenya. We analyzed the data using descriptive statistics and random forest models to elucidate the characteristics of the participant population, underlying motivations, and the challenges and opportunities to develop recommendations for sustainable community-based water monitoring programs. As citizen scientists who engaged long-term were 30-49 years old, had primary or secondary school education and passed by the monitoring station frequently, targeting sensitization activities at people with such background could increase participation in community-based water monitoring. Sensitization meetings were key in engaging long-term volunteers, but participants indicated that continued feedback through education and communication of the project findings is required to keep volunteers motivated. The use of cellphone credit to submit data was identified as challenge for participation, highlighting the need for data submission methods that do not incur costs for the participants. Greater volunteer support could also be achieved by active involvement of the members of Water Resource Users Associations, since membership increased the likelihood of continuous engagement in water monitoring under the participants. Furthermore, many participants indicated that their motivation was to help water management and conservation, as most people rely directly on rivers for their water supply. Providing a platform to contribute to better water resources management could therefore result in direct benefits (e.g. improved water supply) for the participants, and thus an incentive to participate actively.